Size-controlled synthesis of ultrafine silver powders for electronic paste using a one-pot aqueous method - Zhe Huang; Jin Yang; Baishan Chen; Minggang Li; Siwei Tang; Yunzhu Ma; Wensheng Liu (Materials & Design)
Silver nanoparticles possess unique electrical, thermal, and catalytic properties, making them valuable in various fields such as flexible electronics printing, electronic device interconnections, and solar energy applications. Controlling the size of silver nanoparticles is critical to its properties and determining the application. This study investigates the influence of reaction rates on the size of silver nanoparticles synthesized in aqueous solutions. The precursor of silver ammonia concentrations from 5 to 160 mM was explored, revealing a positive correlation between reactant concentration and particle size that challenges traditional theories. It results from aggregation growth facilitated by high concentrations, leading to significant increases of particle size, with a trigger of 10 mM. Furthermore, when fix the precursor concentration, the instantaneous and homogeneous concentrations of the reducing agent have completely opposite effects. Specifically, decreasing the instantaneous concentration while increasing the homogeneous concentration compress the reaction zone and refined particle size distributions. It successfully shrank the particle size from 510 to 140 nm for the condition of 20 mM precursor concentration. Additionally, lower temperatures bring a anisotropic self-assemble, while higher temperatures result in a random growth. At last, the size of silver particles exhibits distinct effects on the printing performance and conductivity of silver paste.